The social determination of health and the transformation of rights and ethics: a meta-critical methodology for responsible and reparative science - Breilh Paz y Miño, Jaime Eduardo (2023)
The hyper-neoliberal era has seen the collapse of the ethos of life and the formation of a civilisation of extreme greed. In this global context, the preeminence of a technologically endowed but epistemologically and ethically misguided form of science has contributed to forms of ‘scientific illiteracy’ and strategies of planned ignorance that nourish a neo-conservative form of governance. The challenge of transforming the paradigm of bioethics and the right to health beyond the biomedical horizon is an urgent priority. Building on the strengths of a social determination approach and a meta-critical methodology and rooted in critical epidemiology, this essay proposes powerful tools for a radical shift in thought and action linked to rights and ethics. Together, medicine, public health, and collective health provide a path forward to reform ethics and advance the rights of humans and nature.